Enteral nutrition feeding in Chinese intensive care units: a cross-sectional study involving 116 hospitals - Xing, Juan; Zhang, Zhongheng; Ke, Lu; Zhou, Jing; Qin, Bingyu; Liang, Hongkai; Chen, Xiaomei; Liu, Wenming; Liu, Zhongmin; Ai, Yuhang; Wang, Difeng; Wang, Qiuhui; et al. (Critical care (London, England), 2018)
There is a lack of large-scale epidemiological data on the clinical practice of enteral nutrition (EN) feeding in China. This study aimed to provide such data on Chinese hospitals and to investigate factors associated with EN delivery. This cross-sectional study was launched in 118 intensive care units (ICUs) of 116 mainland hospitals and conducted on April 26, 2017. At 00:00 on April 26, all patients in these ICUs were included. Demographic and clinical variables of patients on April 25 were obtained. The dates of hospitalization, ICU admission and nutrition initiation were reviewed. The outcome status 28 days after the day of investigation was obtained. A total of 1953 patients were included for analysis, including 1483 survivors and 312 nonsurvivors. The median study day was day 7 (IQR 2-19 days) after ICU entry. The proportions of subjects starting EN within 24, 48 and 72 h after ICU entry was 24.8% (84/352), 32.7% (150/459) and 40.0% (200/541), respectively. The proportion of subjects receiving > 80% estimated energy target within 24, 48, 72 h and 7 days after ICU entry was 10.5% (37/352), 10.9% (50/459), 11.8% (64/541) and 17.8% (162/910), respectively. Using acute gastrointestinal injury (AGI) 1 as the reference in a Cox model, patients with AGI 2-3 were associated with reduced likelihood of EN initiation (HR 0.46, 95% CI 0.353-0.599; p < 0.001). AGI 4 was significantly associated with lower hazard of EN administration (HR 0.056; 95% CI 0.008-0.398; p = 0.004). In a linear regression model, greater Sequential Organ Failure Assessment scores (coefficient - 0.002, 95% CI - 0.008 to - 0.001; p = 0.024) and male gender (coefficient - 0.144, 95% CI - 0.203 to - 0.085; p < 0.001) were found to be associated with lower EN proportion. As compared with AGI 1, AGI 2-3 was associated with lower EN proportion (coefficient - 0.206, 95% CI - 0.273 to - 0.139; p < 0.001). The study showed that EN delivery was suboptimal in Chinese ICUs. More attention should be paid to EN use in the early days after ICU admission.